Case Writing And Analysis: TIME DOTCOM Berhad - Sern, Tan Hong (2003)
This is a comprehensive case writing and analysis on one of the local telecommunications providers - TIME dotCOm Berhad(413292-P). The study reviews the subject from business, technical and organization perspective of the Company and provides apreview into the current state of telecommunications industry in the local scene.